Fundamentals of Structural Engineering - Connor, Jerome J. (Springer New York : Imprint: Springer, 2013)
Fundamentals of Structural Engineering provides a balanced, seamless treatment of both classic, analytic methods and contemporary, computer-based techniques for conceptualizing and designing a structure. The books principle goal is to foster an intuitive understanding of structural behavior based on problem solving experience for students of civil engineering and architecture who have been exposed to the basic concepts of engineering mechanics and mechanics of materials. Making it distinct from many other undergraduate textbooks, the authors of this text recognize the notion that engineers reason about behavior using simple models and intuition they acquire through problem solving. The approach adopted in this text develops this type of intuition by presenting extensive, realistic problems and case studies together with computer simulation, which allows rapid exploration of how a structure responds to changes in geometry and physical parameters. This book also: Emphasizes problem-based understanding of structural behavior Organizes chapters by structural types Provides balanced, seamless treatment of both classic and contemporary computer-based analysis methods Offers extensive sample problems and detailed solutions to problems of structural analysis Cultivates intuitive thinking about structural behavior Incorporates input data operable with numerous widely used engineering design software packages Features 900 figures and graphs The integrated approach employed in Fundamentals of Structural Engineering makes it an ideal and comprehensive book for students and an authoritative reference for practitioners of structural engineering.